Revelation in a Modern nation State: Muhammadiyah and Islamic Legal Reasoning in Indonesia - Hosen, Nadirsyah (Studia Islamika, 2003)
This article examines the attempt by Muhammadiyah to respond to the issue of returning to the primary sources -the Qur'an and the hadith -to resolve modern problems. The focus will be on the concept, method and source of ijtihad (legal reasoning) used by Muhammadiyah. The author will argue that Muhammadiyah faces several problems in formulating a method to reinterpret the Qur'an and the hadith and these will be critically analysed.DOI: 10.15408/sdi.v10i1.643